La libre circulation des personnes au sein de l’espace de la C.E.M.A.C : entre mythes et réalités - Serge Loungou (Belgeo)
The issue of free movement of people is one of the stumbling blocks between the Members of the Central Africa Economic and Monetary Community (C.A.E.M.C). This disagreement is related to many reasons, some of which are part of imaginary constructions developed especially in Gabon and Equatorial Guinea. Three great myths are underlying the apparent reluctance of these two states to apply the principles of free movement of people: the myth of demographic invasion and the myths of economic and social perversion associated with the crime of foreign origin. Deeply rooted in the national consciousness, these representations are expressed through migration policies and border practices which are particularly discriminatory against nationals of the sub region.